2016
DOI: 10.5586/aa.1657
|View full text |Cite
|
Sign up to set email alerts
|

The occurrence of fungi on roots and stem bases of Triticum aestivum ssp. spelta L. Thell. grown under two levels of chemical protection and harmfulness of Fusarium graminearum Schwabe to seedlings of selected genotypes

Abstract: Investigations were carried out in 2007–2009 on the plots of the Felin Experimental Station belonging to the University of Life Sciences in Lublin, Poland. The studies comprised two breeding lines of spelt wheat (<em>Triticum aestivum</em> ssp. <em>spelta</em> L. Thell.) – STH 3 and STH 715. Two levels of chemical protection were applied in the cultivation with minimal and complex protection. Infection of winter spelt wheat roots and stem bases was recorded in each growing season at har… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Wheat plants are susceptible for different disease pathogens infecting root, leaf and head causing serious diseases and greatly affect productivity all over the world. Root diseases can cause losses of 3 to 4%, depending on the variety, the severity of the disease and the appropriate climate for disease development (Kaur 2016). Additionally, many studies showed that the root disease causes a loss of global yield from 10 to 15% and the fungus Rhizoctonia solani causes loss of yield of 25-100% of the global wheat production every year.…”
Section: Introductionmentioning
confidence: 99%
“…Wheat plants are susceptible for different disease pathogens infecting root, leaf and head causing serious diseases and greatly affect productivity all over the world. Root diseases can cause losses of 3 to 4%, depending on the variety, the severity of the disease and the appropriate climate for disease development (Kaur 2016). Additionally, many studies showed that the root disease causes a loss of global yield from 10 to 15% and the fungus Rhizoctonia solani causes loss of yield of 25-100% of the global wheat production every year.…”
Section: Introductionmentioning
confidence: 99%